SAT0488 Tuberculosis in A Registry of Rheumatic Patients Treated with Biological Drugs. (15th July 2016) - Benzaquén, N.; Haye Salinas, M.; Pirola, J.; Retamozo, S.; Caeiro, F.; Alvarellos, A.; De la Vega, M.; Casado, G.; Gomez, G.; Citera, G.; Gallardo, M.; Quinteros, A.; et al.
Abstract : Background: Biologic therapies (bDMARDs) have improved the treatment of rheumatic diseases; however, the risk of tuberculosis (TB) infection or reactivation in patients treated with this drug class remains a concern. Objectives: We investigated the clinical characteristics and prognostic factors of TB in an Argentine registry of rheumatic diseases patients treated with bDMARDS. Methods: Database included demographics of patients, type and duration of treatments and clinical information of adverse events. A control group was included for comparison consisting of patients not treated with bDMARDs but similar demographics. Values are expressed as mean±standard deviation, median (ranges), and frequencies (percentages), as appropriate. Multivariate logistic regression analysis was used to identify variables associated with the occurrence of TB; OR and 95% CI were calculated by exponentiation of regression coefficients. Results: As of January 2016, 3483 patients, 4762 treatments and 2580 adverse events were studied. Mean age 56.1±15, 7 years; 2748 (78.9%) patients were women. Initial treatments were 1472 (42.3) bDMARD vs. 2011 (57.7) non-bDMARD. Main diagnosis: Rheumatoid arthritis (RA) 2706 (77.7), Psoriatic arthritis (PsA) 293 (8.4), juvenile idiopathic arthritis (JIA) and lupus with 117 (3.36) each. Of 4762 treatments, most frequent biological drugs were etanercept 119 (25, 1), adalimumab 626 (13, 2), and abatacept with 282 (5.9). Of 3483 patients, 18 (0.5) presented TB as an adverse event, their mean age was 52.9±2.8; 16 (88.9) had AR and 2 (11.1) had PsA; 16 (88.9) had initially received bDMARD vs. 2 (11.1) who had received non- bDMARD treatments. PPD test was performed in 2002/2883 (69.4) bDMARD treatments vs. 372/1879 (19.8%) non-bDMARD treatments, with 126 (6.3) vs 35 (9.4) positive tests, respectively. Median time from treatment commencement to TB was 15.1 (range 1.6–137.5) months. Treatments during which, TB was diagnosed were etanercept 5 (27.8), adalimumab 4 (22.2), non-bDMARD 3 (16.7), abatacept and infliximab with 2 (11.1) each and tocilizumab 1 (5.6), the distribution was not significantly different (Table 1 ). The risk of developing TB was higher in patients whose first treatment was bDMARDs (OR 5.6 95%CI 1.3–24.3). Conclusions: A higher frequency of TB was seen in patients treated with bDMARDs; however, results should be interpreted cautiously because of registries inherent limitations. Disclosure of Interest: None declared